2017
DOI: 10.1021/acs.jpcc.7b06168
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Bulk Heterojunction Morphology by Self-Assembly of Oppositely Charged Nanoparticles

Abstract: Using kinetic Monte Carlo simulations of a simple coarse-grained model, we demonstrate that the self-assembly of oppositely charged nanoparticles is a promising approach to design efficient bulk heterojunction (BHJ) solar cells. Simulations are performed starting from a random configuration of oppositely charged nanoparticles in solution for a range of concentrations. Interconnected percolated morphologies form at high nanoparticle concentrations, when the aggregate growth ceases after certain time. If only Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The major driving forces for LbL assembly of NDDS include electrostatic force, hydrogen bonding, charge transfer interaction and covalent bonding. Recently, the works done by Prof. Soumitra Satapathi et al and Prof, Veera Sadhu et al, especially those related with nanoparticles, are very helpful for illustrating the different types and wide applications of LbL assembled NDDS (Kim et al, 2015;Singh et al, 2017;Paliwal et al, 2019;Sur et al, 2019).…”
Section: Formation Mechanism Of Lbl Assembled Nddsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major driving forces for LbL assembly of NDDS include electrostatic force, hydrogen bonding, charge transfer interaction and covalent bonding. Recently, the works done by Prof. Soumitra Satapathi et al and Prof, Veera Sadhu et al, especially those related with nanoparticles, are very helpful for illustrating the different types and wide applications of LbL assembled NDDS (Kim et al, 2015;Singh et al, 2017;Paliwal et al, 2019;Sur et al, 2019).…”
Section: Formation Mechanism Of Lbl Assembled Nddsmentioning
confidence: 99%
“…Recently, the works done by Prof. Soumitra Satapathi et al. and Prof, Veera Sadhu et al., especially those related with nanoparticles, are very helpful for illustrating the different types and wide applications of LbL assembled NDDS (Kim et al., 2015 ; Singh et al., 2017 ; Paliwal et al., 2019 ; Sur et al., 2019 ).…”
Section: Formation Mechanism Of Lbl Assembled Nddsmentioning
confidence: 99%
“…Organic-nanoparticle-based devices are the emerging technology for next-generation optoelectronic applications, especially in the field of organic solar cells. Organic-nanoparticle-based device processing overcomes two major roadblocks for current state-of-the-art organic photovoltaic technology through its use of an environmentally benign aqueous solvent to replace the toxic haloarene solvents previously used for large-scale printing on flexible substrates , and its tunable morphology of the active layer materials at multiple length scales. ,, Organic nanoparticles are generally synthesized by the miniemulsion method . These nanoparticles are stabilized by ionic or neutral surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…But during the evolution to reach equilibrium, system passes through various non-equilibrium complex structures which are very different from equilibrium structures 34 . For instance, various studies have shown that system of oppositely charged nanoparticles are often trapped in non-equilibrium “gel”-like (percolated) structures at high packing fractions, and do not evolve to minimum energy crystalline structures due to slow system dynamics 3537 . In one of our previous study, we have found that these kinetically trapped percolated structures formed by self-assembly of electron conducting and hole conducting polymer NPs are the bulk heterojunction morphologies for efficient organic solar cells 37 .…”
Section: Introductionmentioning
confidence: 99%